The factors associated with chronic energy deficiency in breastfeeding mothers
Background: Chronic energy deficiency (CED) in breastfeeding mothers is very likely to occur because apart from the mother meeting the recovery needs of giving birth, the mother also provides breast milk to her baby. This study aimed to determine the factors associated with the incidence of CED in breastfeeding mothers. Methods: The research was conducted on 203 breastfeeding mothers who were randomly selected from 10 villages in Kefamenanu Regency, East Nusa Tenggara (NTT), Indonesia. Data collection was done directly by nutrition officer with interviews using g-form. Data were analysed using the Chi Square. Results: It was found that the factors associated with the incidence of CED in breastfeeding mothers were age OR=0.5 times (CI 95%: 0.257-1.054) and parity of the number of children in the family OR=2.1 times (95%: 1-4.4)